"Where is the Sudheni Didi?”: Community Perspectives and Revisiting Nepal’s Maternal Health Policies - Neupane, Sunisha (Atlantis)

(untitled) (Mount Saint Vincent University, 2026)
This article examines Nepal’s maternal health policies in the context of a remote community in western Nepal. There has been a substantial decline in maternal mortality and an increase in institutional deliveries, in Nepal, but, along with these achievements, inequities in maternal health continue. Drawing on immersive participatory research conducted in 2015 in two villages in Baglung district, the study integrates observation, fieldnotes, focus group discussions, participatory workshops and interviews with women, health workers and national maternal health experts. Findings show that distance, terrain, limited health post hours, and unreliable transport make access to institutional services practically challenging in remote Nepal. Female Community Health Volunteers (FCHVs) occupy an in-between position, understanding women’s lived experiences while doing their best to follow protocols and mandates. Community members express the need for home-based support when facilities cannot be reached. The disappearance of the sudheni reflects a broader policy shift that privileges service availability and biomedical definitions of skilled care. The article argues that maternal health policy must move beyond institutional targets toward context-responsive approaches that centre women’s lived experiences and make maternity care accessible to remote populations.